2002
DOI: 10.1023/a:1020285909696
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Intraperitoneal injection of Semax (synthetic analogue of ACTH4-7, MEHFPGP) in a dose of 50 mg/kg produced a protective effect on rats with experimental indomethacin-induced ulcers. Experiments on narcotized rats showed that Semax in the studied dose had no effect on basal blood flow in the stomach, but prevented reduction of blood flow induced by indomethacin. The antiulcer effect of Semax is probably related to improvement of blood flow in the gastric wall disturbed by indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Previous studies showed that a NO donor Sydnopharm has antiulcer activity [6]. Combined treatment with L-arginine and ibuprofen significantly reduces the adverse effect of NSAID on GM [10].…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies showed that a NO donor Sydnopharm has antiulcer activity [6]. Combined treatment with L-arginine and ibuprofen significantly reduces the adverse effect of NSAID on GM [10].…”
Section: Resultsmentioning
confidence: 97%
“…Realization of these properties at the tissue and organ levels seemed to prevent the disorders unfolding under the effects of mast cell mediators. The protective effect of PGP not mediated through mast cell stabilization could include peptide regulation of the vascular tone [1], endothelium permeability maintenance, maintenance of adequate bloodfl ow [2], and improvement of cell and tissue resistance to oxidative stress [5].…”
Section: Resultsmentioning
confidence: 99%
“…A single intraperitoneal injection of the drug at a dose of 100 μg/kg reduced the mortality rate of animals, hyperfermentation, the activation of lipid peroxidation, and vascular permeability, and improved microcirculation and accelerated the healing of the zones of destruction of the pancreas [209]. The study of the effects of Semax on various models of ulceration showed a marked antiulcer effect of the drug [210][211][212].…”
Section: Discussionmentioning
confidence: 99%